Determinant of carbon stabilization in tropical soils: a review of carbon sequestration potential of soil aggregate fractions (2018)
Soils contribute to global climate mitigation through Sequestration of carbon. Soils that remain undisturbed for long period of time could be the best choice for carbon Sequestration. Quality of organic matter, land management practices and land use types had been considered the major factors influencing accumulation and stabilization of carbon associated with soil aggregate fractions. This understanding had limited the efforts at tracking carbon accumulation and stabilization of various aggregate fractions. However, other factors are becoming relevant in the evaluation carbon stabilization potential of various soil aggregate fraction in different soil texture and types. Therefore these factors require detail description. Organic and inorganic carbon compounds contribute to the soil carbon stabilization and subsequently, enhance carbon Sequestration. Understanding of the critical factors that control stabilization of carbon in soil aggregate fractions is limited. This limits the efforts on how to optimize carbon Sequestration potential among soil aggregate fractions and soil types and consequently, one of the reasons for unabated evolve of greenhouse gases from soils to the atmosphere. Therefore, brief description of factors that influence and optimize the Sequestration of carbon in tropical soils were reviewed. Hence, quantity and quality of organic matter, availability of basic cations; proportion of fine particle fraction in the soil; land management practices Option; organic and inorganic carbon concentration and soil moisture content were identified as the major factors influencing the soil carbon stabilization in tropical soils. The processes involve in carbon stabilization of tropical soils could be classified into Chemical and physical protecting mechanisms. Organic compounds derive from plant origin enhance soil particle aggregation while cations facilitate organo-mineral formation among soil fine particles. Surface area specificity is essential facilitator of organo- mineral formation among soil fine particles.